A message from the 'underground forge of the gods': history and current eruptions at Mt Etna. (31st July 2021) - Thomaidis, Konstantinos; Troll, Valentin R.; Deegan, Frances M.; Freda, Carmela; Corsaro, Rosa A.; Behncke, Boris; Rafailidis, Savvas
Abstract : Mt Etna has made headlines over the last weeks and months with spectacular eruptions, some of them highly explosive. This type of paroxysmal eruptive behaviour is characteristic of Etna's activity over the past few decades and so it is no surprise that Etna is among the most active volcanoes worldwide. Etna is well‐known for its extraordinary geology and due to its repeated eruptive activity it provides a continuous supply of new scientific opportunities to understand the inner workings of large basaltic volcanic systems. In addition to its scientific value, Etna is also a world famous tourist attraction and has been listed as a UNESCO World Heritage site in 2013 for its geological and cultural value and not least for its fine agricultural products. Etna's status as an iconic volcano is not a recent phenomenon; in fact, Etna has been a literary fixture for at least 3000 years, giving rise to many ancient myths and legends that mark it as a special place, deserving of human respect. From the ancient eruptions to the latest events in February–April 2021, people try to explain and understand the processes that occur within and beneath the volcano. In this article, we briefly summarize the recent eruptive activity of Etna as well as the ancient myths and legends that surround this volcano, from the underground forge of Hephaestus to the adventures of Odysseus, all the way to the benefits and dangers the volcano provides to those living on its flanks today.